Serial Interval of COVID-19 among Publicly Reported Confirmed Cases - Du, Zhanwei; Xu, Xiaoke; Wu, Ye; Wang, Lin; Cowling, Benjamin J.; Meyers, Lauren Ancel (Emerging infectious diseases, 2020)
We estimate the distribution of serial intervals for 468 confirmed cases of coronavirus disease reported in China as of February 8, 2020. The mean interval was 3.96 days (95% CI 3.53-4.39 days), SD 4.75 days (95% CI 4.46-5.07 days); 12.6% of case reports indicated presymptomatic transmission.